Determinants of Capital Structure in the Presence of Supply Chain Activities of Listed Construction Firms in Vietnam - Kim Hoa, Ngo Thi; Huong, Ngo Thi Thu (ExcelingTech, 2020)
The study aims to identify the capital structure determinants in the presence of the supply chain of the listed construction firms in Vietnam. The determinants of capital structure are factors affecting firm financial leverage, including firm profitability, size, growth rate, fixed assets, liquidity, interest coverage and state ownership along with the supply chain activities. The study is based on a data of 53 listed construction firms in the Hanoi and Ho Chi Minh Stock Exchange over the period 2014-2018. The results indicated that the supply chain activities along with other determinants except profits and liquidity have a positive association with the capital structure of the listed construction firm in Vietnam. These findings guided to the policymakers that they should enhance the intensions towards the determinant of the capital structure along with supply chain activities to improve the organizational performance.